FIKIH KELUARGA : PERSPEKTIF HUKUM ISLAM TERHADAP POLA ASUH ANAK DALAM MASYARAKAT MODERN - Said, Dede Hafirman; Rahmah, Azizatur (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2024)
Abstract Parenting styles play a crucial role in shaping a child's character and behavior, which in turn influences their future social and psychological life. In today's modern era, parenting patterns are increasingly influenced by a variety of factors, such as social changes, technological advancements, and shifts in cultural values. This study aims to explore Islamic perspectives on child-rearing practices in the context of contemporary society, with a focus on the fundamental principles of family jurisprudence. The methodology employed is a literature review, which analyzes both classical and modern interpretations of Islamic law, particularly those related to family jurisprudence, and examines their application in the context of child-rearing. The findings of this research indicate that Islamic law offers clear guidelines for raising and nurturing children, emphasizing the importance of balancing love, discipline, and religious education. Islam also stresses the protection of children's rights, including the right to quality education and a healthy environment. However, the challenges faced by parents in modern society—such as the influence of globalization, technology, and changing cultural values—require a rethinking of these principles to ensure they remain relevant and effective in guiding children. In conclusion, this study highlights that despite differences in cultural and social approaches, the principles of family jurisprudence continue to provide a solid foundation for establishing effective parenting strategies in the face of modern societal dynamics.